2021
DOI: 10.1530/rep-20-0608
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D in follicular development and oocyte maturation

Abstract: Vitamin D (VD) is a secosteroid hormone synthesized predominantly in the skin upon ultraviolet light exposure, which can also be obtained from dietary sources. In target cells, the bioactive VD binds to specific VD receptor to regulate downstream transcription of genes that are involved in a wide range of cellular processes. There is increasing recognition that the proper physiological levels of VD are critical for optimizing reproductive potential in women. The direct VD action in the ovary was first suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…The female may feel disappointed when only one or two follicles are obtained, but here, more is not necessarily better, because every single mature follicle can release one egg, which in turn can be fertilized later [ 33 , 34 ]. Some studies [ 35 , 36 ] have concluded that the sufficiency of vitamin D is important for follicular development with improved steroidogenic function and egg maturation. However, it is difficult to study the direct effect of vitamin D on the ovary since the functions and actions of vitamin D as an endocrine and paracrine factor are highly context-dependent, as types and developmental stages of follicles as well as vitamin D metabolite forms and doses must be carefully considered during experimental design.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The female may feel disappointed when only one or two follicles are obtained, but here, more is not necessarily better, because every single mature follicle can release one egg, which in turn can be fertilized later [ 33 , 34 ]. Some studies [ 35 , 36 ] have concluded that the sufficiency of vitamin D is important for follicular development with improved steroidogenic function and egg maturation. However, it is difficult to study the direct effect of vitamin D on the ovary since the functions and actions of vitamin D as an endocrine and paracrine factor are highly context-dependent, as types and developmental stages of follicles as well as vitamin D metabolite forms and doses must be carefully considered during experimental design.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effect of vitamin D on the eggs number and their MR, it must be mentioned that all clinical research aimed at evaluating the effect of vitamin D on the ovaries was conducted on females suffering from fertility problems, and most of these researches were in the context of PCOs [ 35 , 37 ]. As for our study, it aimed to select reproductively healthy females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In target cells, VD binds to specific VD receptors (VDR) to regulate transcription of genes involved in diverse cellular processes, including pro-differentiation, anti-proliferation, pro-apoptosis, immunosuppression, and anti-inflammation roles [ 277 ]. Along with its essential role in bone physiology and health, there is an increasing recognition that VD is critical for normal folliculogenesis and optimizing reproductive potential in women [ 277 , 278 ].…”
Section: Potential Modifiers Of Age-dependent Changes In Folliculogen...mentioning
confidence: 99%
“…Finally, it is converted to biologically active 1,25dihydroxy VitD in the kidney. The VitD receptor binds to VitD response element regions in DNA and regulates the transcription of many genes [2]. VitD regulates cellular functions through VitD receptor.…”
Section: Introductionmentioning
confidence: 99%